The Impact of Alcohol Consumption on Cognitive Impairment in Patients With Diabetes, Hypertension, or Chronic Kidney Disease - Yen, Fu-Shun; Wang, Shiow-Ing; Lin, Shih-Yi; Chao, Yung-Hsiang; Wei, James Cheng-Chung (Frontiers in Medicine, 2022)
To investigate the impact of alcohol use on the risk of cognitive impairment in older adults with chronic illness, we used the Digit Symbol Substitution Test (DSST) to evaluate cognitive function in older adults (≥ 60 years) in the National Health and Nutrition Examination Survey. Participants were categorized as abstainers, drinkers, and heavy drinkers. Logistic regression analyses were used to explore associations between cognitive impairment and alcohol drinking in patients with or without diabetes, hypertension, and chronic kidney disease (CKD). Multivariate analysis showed that alcohol abstinence was significantly associated with a higher risk of cognitive impairment in patients with diabetes (aOR 2.525, 95% CI 1.148-5.554) and hypertension (aOR 2.870, 95% CI 1.090-7.550) compared with drinkers. The dose-response analyses revealed that low to heavy alcohol use was associated with a lower risk of cognitive decline in patients with diabetes and CKD; low to moderate amount of alcohol use had an association with reduced risk of cognitive impairment, but heavy drinking increased the risk of cognitive impairment in patients with hypertension. The impacts of alcohol drinking on cognitive impairment are significantly different in patients with different comorbidities.